Discourse of a Glossy Magazine: Socio-Communicative Aspects - ЛоллоАнастасия Робертовна (Journal of Economic Sociology, 2011)
The paper offers an insight on a subject of contemporary consumption discourse — women’s glossy magazine. Discourse analysis of the Cosmopolitan’s articles reveals speciﬁ c linguistic means and substantive patterns that serve to construct the collective lifestyle.